Clinical Characterization of Mismatch Repair Gene-Deficient Metastatic Castration-Resistant Prostate Cancer - Ye, Senlin; Wang, Haohui; He, Kancheng; Peng, Mou; Wang, Yinhuai; Li, Yuanwei; Jiang, Shusuan; Li, Jin; Yi, Lu; Cui, Rongrong (Frontiers in Oncology, 2020)
Mismatch repair (MMR) deficient (dMMR) prostate cancer is rare and has not been well studied. We aimed to evaluate the clinical characterization of metastatic castration-resistant prostate cancer (mCRPC) patients with dMMR. The MMR genes including MLH1, MLH3, MSH2, MSH6, PMS1, PMS2 and EPCAM were analyzed by targeted sequencing on plasma cell-free DNA samples. A total of one hundred nine mCRPC patients were identified, including fifty patients with MMR alterations (pathogenic alteration, n=7; alterations of unknown significance, n=43) and fifty-nine patients with wild type MMR. For seven patients with pathogenic MMR alterations, the median age at diagnosis was 63.5, 42.9% had Gleason Score ≥8. The median time of androgen deprivation therapy (ADT) initiation to CRPC was 24 months. Compared with wild-type MMR subgroup, patients with MMR alterations, pathogenic MMR alterations or MMR alterations of unknown significance showed higher rate of hotspot missense mutations or copy number amplification in AR gene (24/50 vs 10/59, P=7.8×10-4; 7/7 vs 10/59, P=2.5×10-5; 17/43 vs 10/59, P=0.013). The presence of any MMR alterations was associated with a inferior response to abiraterone (median progression-free survival [PFS]: 5 vs 10.9 months, P=0.022). Shorter PFS were observed in both pathogenic MMR alterations subgroup (median PFS: 5 months) and MMR alterations of unknown significance (median PFS: 5.3 months) subgroup, compared with those of wild-type MMR genes (median PFS: 10.9 months, P=0.052). There is no statistically significant difference in PFS to docetaxel chemotherapy between MMR alterations of unknown significance and wild-type MMR subgroups (8.2 vs 8.1 months, P=0.23). Our results demonstrated that dMMR mCRPC had equivalent response to standard ADT and taxane-based chemotherapy compared with wild-type MMR patients. Both patients with pathogenic and unknown significance alterations of MMR genes had poorer response to abiraterone therapy.